Model Komunikasi Pemerintahan Kota Tanjung Pinang Dalam Pengembangan Destinasi Wisata - Muhammad Nursyawal; Muhammad Ryandana (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
The Tanjung Pinang Island area has many tourist destinations that have special characteristics in Indonesia, but in its management it still faces many obstacles such as a lack of community involvement in managing existing tourism resources and the low quality of tourism facilities and infrastructure. In particular, the development of the area on Penyengat Island as a leading tourist area is also hampered by various regulations, government communication between governments has not been optimal even though the Penyengat Island tourist attraction has been designated as a national cultural heritage. The maintenance of tourist objects is carried out by the Archaeological Center whose technical unit is in Batu Sangkar, West Sumatra. The impact is that regional government communication, especially in terms of budget allocations for the city government, can’t be carried out well. This research aims to (1) identify government communication models in managing potential tourist attractions on Penyengat Island, (2) examine the characteristics of the community so that the form and level of community participation in maintaining and preserving the environment in supporting tourism on Penyengat Island can be seen. This research was carried out in Penyengat Island, Tanjungpinang City, Riau Islands Province.